Impact of Decipher on use of post‐operative radiotherapy: Individual patient analysis of two prospective registries. Issue 4 (24th January 2021) - Shahait, Mohammed; Liu, Vinnie Y. T.; Vapiwala, Neha; Lal, Priti; Kim, Jessica; Trabulsi, Eduard J.; Huang, Huei‐Chung; Davicioni, Elai; Thompson, Darby J. S.; Spratt, Daniel; Den, Robert B.; Lee, David I.
Abstract: Objective: To assess the association between Genomic Classifier (GC)‐risk group and post‐radical prostatectomy treatment in clinical practice. Methods: Two prospective observational cohorts of men with prostate cancer (PCa) who underwent RP in two referral centers and had GC testing post‐prostatectomy between 2013 and 2018 were included. The primary endpoint of the study was to assess the association between GC‐risk group and time to secondary therapy. Univariable (UVA) and multivariable (MVA) Cox proportional hazards models were constructed to assess the association between GC‐risk group and time to receipt of secondary therapy after RP, where secondary therapy is defined as receiving either RT or ADT after RP. Results: A total of 398 patients are included in the analysis. Patients with high‐GC risk were more likely to receive any secondary therapy (OR: 6.84) compared to patients with low/intermediate‐GC risk. The proportion of high‐GC risk patients receiving RT at 2 years post‐RP was 31.5%, compared to only 6.3% among the low/intermediate‐GC risk patients. Conclusion: This study demonstrates that physicians in routine practice used GC to identify high risk patients who might benefit the most from secondary treatment. As such, GC score was independent predictor of receipt of secondary treatment.